VISUAL AND VERBAL RHETORIC ON TELEVISION: A MODERN PERSPECTIVE - Zokirova Shaxzoda Nodirjon qizi (Western European Studies, 2025)
This article explores the phenomenon of visual and verbal rhetoric on television as a complex and multidimensional communicative practice. Drawing upon the ideas of Uzbek, Russian, and Western scholars, the study emphasizes how television discourse embodies both rhetorical tradition and modern communication strategies. The research analyzes the role of ethos, pathos, and logos in televised speeches, focusing on how credibility, emotional appeal, and logical argumentation shape audience perception. It also highlights the significance of visual elements such as symbols, imagery, and staging, which reinforce verbal messages and create a persuasive multimodal discourse
Keywords: television rhetoric; ethos; logos